EFFECT OF FOAMING AGENT AND DRYING TEMPERATURE ON DRYING RATE AND QUALITY OF FOAM-MAT DRIED PAPAYA POWDER - Hong Van Hao; Nguyễn Minh Thủy; Tran Ngoc Giau; Ngô Văn Tài; Võ Quang Minh (Journal of Microbiology Biotechnology and Food Sciences, 2024)
Recently, foam-mat drying is being considered a mild drying technique, requiring low investment costs but being particularly highly effective. This drying method is very useful for liquid or semi-liquid food products that are highly viscous and easily change qualities by heat. Liquid or finely ground foods are foamed with the assistance of surfactants (foam-creating and foam-stabilizing agents are egg albumin and carboxymethyl cellulose, respectively), followed by drying of the foam with hot air. Box-Behnken design (BBD) of response surface methodology (RSM) was designed in this study, with 3 factors and 3 levels, including egg albumin content (6-10%), carboxymethyl cellulose (CMC) (0.1-0.5%) and drying temperature (50-70oC). The drying rate and β-carotene content of foam and product, respectively, are the indicators observed in 18 experimental runs and 6 repetitions at the central point. Use target settings for each response based on high β-carotene content and highest drying rate to produce a high-quality papaya powder product with the shortest drying time. The optimal and feasible experimental conditions for drying foam mats were achieved with albumin concentration, CMC and optimal drying temperature at 9.07%, 0.39% and 62oC, respectively. From these optimal conditions, the optimal values of drying rate and β-carotene content were achieved as 3.41 g water/g dry matter/min and 37.95 µg/g, respectively. This study has confirmed that foam drying is a feasible method to produce good quality papaya powder, the product maintains the natural color of the original material, low moisture (8.5%) and water activity (0.35), and high rehydration ratio (4.05) when drying at 62oC for 3 hours.
Keywords: Microencapsulation and Drying Processes; Nanocomposite Films for Food Packaging; Polysaccharides Composition and Applications